Molecular Screening of Keratoconus Susceptibility Sequence Variants in VSX1, TGFBI, DOCK9, STK24, and IPO5 Genes in Polish Patients and Novel TGFBI Variant Identification. (2nd January 2016) - Karolak, Justyna A.; Polakowski, Piotr; Szaflik, Jerzy; Szaflik, Jacek P.; Gajecka, Marzena
Abstract: Purpose : Keratoconus (KTCN) is a degenerative disorder of the eye that results in the conical shape and thinning of the cornea and is a leading cause for corneal transplantations. A number of studies suggest that genetic factors play a role in KTCN etiology. Some candidate gene variants have recently been shown to be associated with KTCN. The purpose of our study was to verify the role of VSX1, TGFBI, DOCK9, IPO5, and STK24 sequence variants in Polish KTCN patients. Methods : Forty-two Polish patients with sporadic KTCN and 50 control individuals were enrolled into this study. Both affected and unaffected individuals underwent detailed ophthalmic examination. The mutations screening in the candidate genes was performed by the direct sequencing method. Results : Analysis of VSX1, TGFBI, DOCK9, IPO5, and STK24 genes identified numerous sequence variants . Variants c.-264_-255delGGGGTGGGGT, c.627 + 23G > A, c.809-6_809-5insT, and c.*200G > T in the VSX1 gene, and heterozygous c.1598G > A mutation (Arg533Gln) in exon 12 of TGFBI were detected for the first time in KTCN patients. Two known sequence variants of TGFBI c.1620T > C (Phe540Phe) and c.1678 + 23G > A were observed in KTCN patients and control individuals. The newly reported c.717 + 43A > G substitution in intron 7 of DOCK9 was identified in both KTCN patients and healthy individuals. Conclusions : Our investigation showed that KTCN-related sequence variants of analyzed genes were found in a very small proportion of the studied patients indicating that genes other than VSX1, TGFBI, DOCK9, IPO5, and STK24 are involved in the development and progression of KTCN in Polish patients. Our results support the hypothesis about the genetic heterogeneity of KTCN.